Increased Incidence of Influenza: Effects of Dense Housing Occupancy, Behaviour and Demographic Factors in Coastal Areas - Heltty, Heltty; Nazaruddin, Nazaruddin; Ningtias, Dwi Wulandari; Lestari, Sari Ari; Apriyanti, Apriyanti; Krismiadi, Dedi (Jurnal Kesehatan Metro Sai Wawai, 2023)
Introduction: Influenza is an acute respiratory infection that is a seasonal pandemic and can be prevented by healthy behaviors. However, the fact is that influenza cases are still often outbreaks, even epidemics, both nationally and globally. Purpose: To assess demographic determinants, occupancy density, and preventive behavior with influenza incidence in the coastal area of Bungkutoko sub-district of Kendari city, in one of the islands of Southeast Sulawesi, Indonesia. Methods: A cross-sectional study involving 95 respondents selected by simple random sampling was used as a research design. Structured interviews used valid and reliable questionnaires to obtain data on age, sex, preventive behavior, and occupancy density. The chi-square test was used to analyze bivariates with a significant value of 0.05. Results: More than half (53.7%) of influenza cases were found out of 95 respondents. Age (p=0.002; OR= 3.251), gender (p=0.041; OR=2.133), preventive behavior (p=0.047; OR=2.163), and dense housing occupancy (p=0.000; OR= 5.775) was significantly associated with influenza (p-value < 0.05). Conclusion: Influenza cases increased associated with risk factors for age, sex, preventive behavior, and dense housing occupancy in coastal areas in this study. Thus, indicating increased education on influenza prevention by paying attention to risk factors by community and interprofessional nurses is needed as early awareness of the potential for an epidemic. Latar belakang: Influenza merupakan penyakit infeksi saluran pernapasan akut yang pandemic musiman dan dapat dicegah dengan prilaku hidup sehat. Namun, kenyataanya kasus influenza masih sering menjadi outbreak, bahkan epidemic baik nasional maupun global. Tujuan: Untuk menilai determinan demografi, kepadatan hunian, dan prilaku pencegahan dengan kejadian influenza di wilayah pesisir kelurahan Bungkutoko kota Kendari, di salah satu kepulauan Sulawesi Tenggara, Indonesia. Metode: Studi cross-sectional digunakan sebagai desain penelitian, melibatkan 95 responden yang dipilih dengan simple random sampling. Wawancara terstruktur menggunakan kuesioner yang valid dan reable untuk memperoleh data usia, jenis kelamin, perilaku sehat, dan kepadatan hunian. Uji chi squre digunakan untuk menganalisis bivariat dengan nilai signifikan 0,05. Hasil: Ditemukan setengah lebih (53,7%) kasus influenza dari 95 responden. Usia (p=0,002; OR= 3,251), jenis kelamin (p=0,041; OR=2,133), perilaku hidup sehat (p=0,047; OR=2,163), dan kepadatan hunian (p=0,000; OR= 5,775) berhubungan secara signifikan terhadap kejadian inluenza (Î± < 0,05). Simpulan: Kasus influenza terjadi peningkatan berhubungan dengan faktor risiko usia, jenis kelamin, perilaku pencegahan, dan kepadatan hunian di daerah pesisir pada studi ini. Sehingga, mengindikasikan peningkatan edukasi pencegahan kejadian influenza dengan memperhatikan faktor risiko oleh perawat komunitas dan interprofessional sangat diperlukan sebagai kewaspadaan dini potensi terjadi epidemic.